2009
DOI: 10.1111/j.1475-4983.2009.00904.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphospace occupation in thalattosuchian crocodylomorphs: skull shape variation, species delineation and temporal patterns

Abstract: Skull shape variation in thalattosuchians is examined using geometric morphometric techniques in order to delineate species, especially with respect to the classification of Callovian species, and to explore patterns of disparity during their evolutionary history. The pattern of morphological diversity in thalattosuchian skulls was found to be very similar to modern crocodilians: the main sources of variation are the length and the width of the snout, but these broad changes are correlated with size of suprate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(126 citation statements)
references
References 66 publications
2
123
0
1
Order By: Relevance
“…The combined role of ecology, physiology or behaviour may therefore explain why marine crocodylomorph diversity does not show good correlation with continental flooding. Pierce et al 16 suggested that thalattosuchian extinction in the Early Cretaceous was driven by sea-level fall. The present results show that marine crocodylomorph diversity is at least partly affected by sea-level variations.…”
Section: Discussionmentioning
confidence: 99%
“…The combined role of ecology, physiology or behaviour may therefore explain why marine crocodylomorph diversity does not show good correlation with continental flooding. Pierce et al 16 suggested that thalattosuchian extinction in the Early Cretaceous was driven by sea-level fall. The present results show that marine crocodylomorph diversity is at least partly affected by sea-level variations.…”
Section: Discussionmentioning
confidence: 99%
“…They are the only archosaurian reptile group to have evolved a fully pelagic lifestyle, and underwent a dramatic diversification between their Middle Jurassic origination from terrestrial ancestors until their sudden extinction during the Early Cretaceous [1]. The diversification of metriorhynchids during their short evolutionary history involved increasing morphological, functional and ecological diversity, including increasing variation in craniofacial form [1][2][3], dental morphology [4], body size [5] and cranial mechanical behaviour to applied loads [1,3]. Remarkably, several species of metriorhynchids often coexisted in the same marine ecosystems, and recent studies have suggested that niche partitioning, maintained via morphological and functional differentiation in the features described above, enabled high biodiversity [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Answering these questions depends on a firm understanding of the relationship between form and function, which requires an integrated toolkit of morphological, functional and phylogenetic data. This repertoire is rarely available for extinct vertebrate clades, but recent work on metriorhynchid cranial morphometrics [1,2], skull biomechanics [1,3], and phylogeny [5] provides an unprecedented reservoir of data for studying these unique crocodylomorphs.…”
Section: Introductionmentioning
confidence: 99%
“…During this period, thalattosuchians achieved a broad ecological range, with a variety of feeding modes, craniofacial forms, dental morphologies, functional biomechanical behaviours, and a wide spectrum of body sizes (Pierce, Angielczyk & Rayfield, 2009;Andrade et al, 2010;Young et al, 2010Young et al, , 2011. Geosaurines, a subgroup of metriorhynchoids, possessed a suite of dental characteristics indicating a macrophagous feeding strategy, and it is likely that they were the apex or second-tier predators of Late Jurassic seas Young et al, 2010Young et al, , 2011.…”
Section: (C) Crocodylomorphsmentioning
confidence: 99%